A secure and efficient revocation protocol for group signatures in vehicular ad hoc networks / Nur Fadhilah Mohd Shari - Nur Fadhilah , Mohd Shari (2018)
Vehicular ad hoc networks (VANETs) allow wireless communication between vehicles and roadside infrastructure to improve road safety and traffic efficiency. Due to the open wireless nature of a VANET, the network is exposed to several security attacks. The presence of attackers could pose a threat and further cause harm to the network. The attackers are categorised as internal and external. An internal attacker is a legitimate member of the network who possess valid credentials and may exploit its legitimacy to mislead and jeopardize the safety of other users, thus causing more damage than an external attacker. This thesis addresses a new revocation protocol for group signatures in VANETs. A revocation protocol protects VANETs against the internal attackers, where it enables such attackers to be removed from the network. A secure and efficient revocation protocol should be emphasized to ensure that VANETs are resilient to internal attackers and thus, vehicles can fully utilize the benefits of VANETs. We begin by analysing some existing revocation protocols based on various cryptographic primitives in the literature. From our analysis, we discover that one of the group signature schemes , called MLGS, lack of revocation protocol where no explicit revocation mechanism was presented. This gap in the literature highlights the need to design a secure and efficient revocation protocol for the scheme, as well as other schemes with similar setup and construction. Prior to the construction, we design a generic abstraction of a revocation protocol for group signatures. The generic abstraction serves as a guideline to design our revocation protocol. We then analyse the security of our proposed protocol and evaluate its performance. We ensure the performance of our revocation protocol is comparable (or better) to those of existing protocols in the literature.